Pengaruh Bimbingan Belajar terhadap Hasil Belajar pada Siswa Tingkat Sekolah Menengah Atas (SMA) - Anggraini Novita Sari; Didit Darmawan (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
The increasing demands of education in the modern era have necessitated various efforts to help students achieve optimal academic results. One widely utilized form of support is tutoring, an educational service that provides additional guidance to help students overcome academic challenges and strengthen their understanding of subject matter. The primary objective of this study was to examine the contribution of tutoring to the educational outcomes of high school students using a literature review approach. Data were drawn from ten relevant scientific journals published in various academic sources. All literature was selected based on topic relevance and then analyzed through a process of review, comparison of findings, and synthesis to obtain a comprehensive picture. The study results indicate that tutoring plays a positive role in improving student learning outcomes. Through the provision of additional materials, targeted practice, and more intensive mentoring, students have the opportunity to understand learning concepts more deeply. In addition to impacting academic achievement, tutoring also supports increased motivation, independence, and more effective learning strategies. Other findings indicate that the use of digital technology expands access to learning and increases the flexibility of the learning process. The effectiveness of this program is also influenced by supporting factors, such as learning discipline, time management skills, the learning environment, and family support. Therefore, tutoring can be an effective alternative in supporting the improvement of high school students' learning outcomes.